PENGARUH KOMPENSASI TERHADAP KEPUASAN KERJA PEGAWAI MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA BARBERMAN GOODFELLAS BARBERSHOP (STUDI KASUS PADA KARYAWAN GOODFELLAS BARBERSHOP SURABAYA) - Oktavianto Wahyu Ashary (Jurnal Ilmu Manajemen, 2022)
This study aimed to analyze and examine the effect of compensation on employee job satisfaction through work motivation as an intervening variable for Goodfellas Barbershop (Barberman) employees. This study uses quantitative methods, and the sampling technique used in this study is saturated sampling with 30 respondents as employees of Goodfellas barbershop. Data collection using observation, interviews, and questionnaires. Statistical analysis in this study used Partial Least Squares (PLS) with smartPLS 3.0 software application. The results of this study explain that all hypotheses in this study have a positive and significant effect. However, the study's results indicate that compensation on job satisfaction has a more significant direct impact than the indirect effect through work motivation as a mediating variable. This research can help companies with problems with some employees who are not satisfied with the promotion system for their coworkers. Leads to higher career advancement scores in decent work motivation. The researcher advises the leadership to pay comprehensive attention to employee compensation and motivation so that it can increase the drive for a higher career, monthly evaluations so that barbermans can express their opinions and feelings at work which are useful for helping barbermans to work comfortably, and make regulations regarding the promotion system based on ability or results that generally meet the service requirements set by the company.